2020
DOI: 10.20944/preprints202005.0023.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First Record of Presence of the Invasive Land Flatworm <em>Platydemus manokwari</em> (Platyhelminthes, Geoplanidae) in Guadeloupe

Abstract: The land flatworm Platydemus manokwari (Platyhelminthes, Geoplanidae) is recorded for the first time from the island of Guadeloupe (French West Indies) in the Caribbean arc. Photographs and records were obtained from citizen science and ranged from the end of 2018 to 2020; specimens were deposited in the collections of the Mus&eacute;um National d'Histoire Naturelle in Paris, France. This is the first record in Guadeloupe and the second for an island in the Caribbean, after Porto Rico.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…The species preys on molluscs and earthworms and might be a threat to the biodiversity of soil animals, especially molluscs which include endemic and rare species in the Caribbean islands ( Delannoye et al, 2015 ). However, no proliferation was recorded and the threat may be minor, but it might also be that A. expatria is only in the first stages of invasion and that it will become an invading species in the future; similarly, recent observations have shown that the highly invasive species Platydemus manokwari is now invading Guadeloupe ( Justine & Winsor, 2020 ). The presence of A. expatria in two islands of the Caribbean suggests that it might be present in other islands, and perhaps in continental North America.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The species preys on molluscs and earthworms and might be a threat to the biodiversity of soil animals, especially molluscs which include endemic and rare species in the Caribbean islands ( Delannoye et al, 2015 ). However, no proliferation was recorded and the threat may be minor, but it might also be that A. expatria is only in the first stages of invasion and that it will become an invading species in the future; similarly, recent observations have shown that the highly invasive species Platydemus manokwari is now invading Guadeloupe ( Justine & Winsor, 2020 ). The presence of A. expatria in two islands of the Caribbean suggests that it might be present in other islands, and perhaps in continental North America.…”
Section: Discussionmentioning
confidence: 99%
“…In 2003, one of us (JLJ) undertook a citizen science program in France about alien land flatworms. Records were unexpectedly received from other locations including French overseas territories ( Justine et al, 2014 , 2015 , 2018a , 2018b , 2019 ; Justine & Winsor, 2020 ). Among these were several records of large land flatworms from the two Caribbean islands of Martinique and Guadeloupe with similar dimensions and pigmentation to A. expatria and tentatively identified as such.…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted February 16, 2022. ; https://doi.org/10.1101/2022.02.14.480416 doi: bioRxiv preprint similar situation was found for the New Guinea flatworm, Platydemus manokwari. Only two years after the first report (Justine & Winsor, 2020), it was found that the flatworm had already invaded most of Guadeloupe (Justine et al, 2021). Similarly, the invasive flatworm Amaga expatria was found in many locations in the two islands (Justine et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…Platydemus manokwari is present on many other islands and archipelagos in the Indo-Pacific, as well as in Puerto Rico, Florida, Australia, France, Thailand, Hong Kong, and Guadeloupe (see references in [ 17 , 64 , 66 , 67 , 68 ]). With notable exceptions, most of these introductions of P. manokwari were probably accidental, but clearly P. manokwari is a voracious polyphagous species [ 63 ] and substantial non-target impacts are to be expected from its introduction.…”
Section: Historical Review: Biocontrol Of Non-marine Molluscs In Oceaniamentioning
confidence: 99%